Penerapan Metode Apriori untuk Mengidentifikasi Korelasi Nilai Siswa di Sekolah Menengah Pertama - Novita Anggraini; Relita Buaton; Imeldawaty Gultom (Lembaga Pengembangan Kinerja Dosen, 2025)
Currently, education is developing very rapidly, starting from the school level even up to the university level. Quality human resources depend on education. Student learning achievement which is usually indicated by report card grades is one of the benchmarks of educational success. However, student grade data for strategic decision making in schools is often done manually and is not optimal. This study aims to identify correlations between student grades in Junior High Schools and apply the Apriori method in data analysis to determine the relationship between student grades and other variables such as subjects and achievement levels. This study involved data collection consisting of 508 students. The Apriori method successfully identified relevant correlations, such as students in Pancasila Education subjects received a B, ICT received a B, Mathematics received a B, English received a B, Social Studies received a B, Craft received a B, Indonesian received a B, Physical Education received a B, Science received a B, SBK received a B, Religious Education received a B, then the Achievement Level is Low with support 3.90% and confidence 95.20%. The use of RapidMiner software in data analysis provides recommendations for robust relationships or correlations. This research is expected to provide sound recommendations to support the achievement of national education goals by identifying the relationship between student grades and subject matter, as well as improving learning outcomes based on student achievement levels.